Escape from Mr. Lemoncello's library - Grabenstein, Chris. (Random House, 2013)
"Twelve-year-old Kyle gets to stay overnight in the new town library, designed by his hero (the famous gamemaker Luigi Lemoncello), with other students but finds that come morning he must work with friends to solve puzzles in order to escape"--